2014
DOI: 10.1186/s12939-014-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Premature mortality due to social and material deprivation in Nova Scotia, Canada

Abstract: IntroductionInequalities in health attributable to inequalities in society have long been recognized. Typically, those most privileged experience better health, regardless of universal access to health care. Associations between social and material deprivation and mortality from all causes of death— a measure of population health, have been described for some regions of Canada. This study further examines the link between deprivation and health, focusing on major causes of mortality for both rural and urban po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Life expectancy rose from 35.8 years for men and 40 years for women in 1920 to 73.3 for men and 80.1 for women in 2001, adding 37.5 and 40.1 years of expected life for men and women, respectively (Pordata 2015). However, even under such propitious conditions, health disparities and inequities have persisted into the present, as reported everywhere (Mackenbach 2006;Clarck 2011;Saint-Jacques et al 2014). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Life expectancy rose from 35.8 years for men and 40 years for women in 1920 to 73.3 for men and 80.1 for women in 2001, adding 37.5 and 40.1 years of expected life for men and women, respectively (Pordata 2015). However, even under such propitious conditions, health disparities and inequities have persisted into the present, as reported everywhere (Mackenbach 2006;Clarck 2011;Saint-Jacques et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Deprivation, broadly understood as a disadvantage in living, work and leisure conditions (Townsend 1987), has been one of the most extensively studied social determinants of health. Within European countries, many systematic inequalities in health are related to socioeconomic status and occur between social classes and areas, with most deprived population groups and neighborhoods having worse health and higher mortality (Sridharan et al 2001;Nolasco et al 2009;Yngwe et al 2012, Saint-Jacques et al 2014. These inequalities in health have been observed across the social hierarchy, not only at the extremes 4 (Charlton 1994;Marmot 2010), highlighting the need to focus research and actions on the entire gradient, not just on the bottom groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Area‐level SES, an aggregation of individual's SES at a certain geographical level, reflects the social and economic development of a residential area, and influences health by determining exposure to health damaging or protective factors . Several studies have demonstrated that people living in areas with low SES experience higher rates of morbidities, mortalities, and disabilities . In Canada, 40% of premature deaths are accounted for by low area‐level SES .…”
mentioning
confidence: 99%
“…Several studies have demonstrated that people living in areas with low SES experience higher rates of morbidities, mortalities, and disabilities . In Canada, 40% of premature deaths are accounted for by low area‐level SES . Similarly, people residing in lower SES areas are more likely to make an emergency department visit or be hospitalised .…”
mentioning
confidence: 99%